Inherited metabolic disorders and cerebral infarction - Kalidas, Kavita; Behrouz, Réza (Expert review of neurotherapeutics, 2008)
The association of genetic factors and cerebral infarction (CI) has long been established. A positive family history alone is a recognized risk factor for CI and vascular events in general. However, there are certain inherited conditions that further increase the risk of stroke. These conditions are generally metabolic and mitochondrial genetic defects that have variable modes of inheritance. This article reviews major inherited metabolic disorders that predispose an individual to CI. Ten main conditions will be discussed: Fabry's disease, cerebrotendinous xanthomatosis, tangier disease, familial hypercholesterolemia, homocystinuria, methylmalonic acidemia, glutaric aciduria type I, propionic acidemia, ornithine transcarbamylase deficiency and mitochondrial encephalopathy, lactic acidosis and stroke-like phenomenon.